A study on the implementation of Bumiputera quota policy in housing scheme / Abdul Samad Jamaludin - Jamaludin, Abdul Samad (2010)
Issues and housing problems in Malaysia always arise due to same problems all over the time. Issue of overhang property, unsold and abundant project keep colouring our development issue. One of the issues which always make huge argument and controversy is about Bumiputra quota. Media always reported some developers are complaining that they have difficulty to sell their Bumiputra quota development till they have to bear losses. When this issue arising at the time, lot of people are debated about the weaknesses of Bumiputra quota policy causes to particular issue. There was a time where Petaling Jaya Member of Parliament (MP), Tony Pua in 2010 speak out some statement that the Bumiputra quota should be demolished especially for high end and commercial property. He claims that such quota is only benefit to some Bumiputra especially high class Malays. Once the statement is print out on newspaper, there have lot of comments, critics and suggestions to overcome this issue. Even this issue is not new in our country, but it still remains without concrete action taken by regulators to solve it. Actually the total percentage of allocation Bumiputra quota as minimum at 30 percent at total development project is still low compare to actual Bumiputra citizen, but due to not affordable the total 30 percent seems to bring loss to developers. Due to the problems, suppose some research is conducted to reveal the truth and causes of the issue. From the objectives to understood the problem, the truth of the complaint, cause of the problem until recommendation that may overcome the issue, researcher hope in the final of this project, it will bring benefits to be discuss and directly implement for the good of bumiputra ethnic.